The skin of Commerson's dolphins (Cephalorhynchus commersonii) as a biomonitor of mercury and selenium in Subantarctic waters - Cáceres Saez, Iris; Prosser Goodall, Rae Natalie; Dellabianca, Natalia Andrea; Cappozzo, Humberto Luis; Ribeiro, Sergio (Chemosphere)
The skin of bycaught Commerson’s dolphins was tested for mercury (Hg) and selenium (Se) biomonitoring in Subantarctic environments. The correlation of levels detected in the skin with those found in internal tissues – lung, liver, kidney and muscle – was assessed to evaluate how skin represents internal Hg and Se distribution for monitoring purposes. Mercury in skin had a concentration range of 0.68–3.11 μg g−1 dry weight (DW), while Se had a higher concentration range of 74.3–124.5 μg g−1 DW. There was no significant correlation between selenium levels in any of the analyzed tissues. Thus, the skin selenium concentration did not reflect the tissular Se levels and did not provide information for biomonitoring. The lack of correlation is explained by the biological role of Se, provided that each tissue regulates Se levels according to physiological needs. However, the skin Hg level had significant positive correlation with the levels in internal tissues (ANOVA p < 0.05), particularly with that of muscle (R2 = 0.79; ANOVA p = 0.0008). Thus, this correlation permits the estimation of Hg content in muscle based on the multiplication of skin biopsy levels by a factor of 1.85. Mercury bioindication using skin biopsies is a non-lethal approach that allows screening of a large number of specimens with little disturbance and makes possible an adequate sampling strategy that produces statistically valid results in populations and study areas. The correlation between Hg levels in the skin and internal tissues supports the use of the epidermis of Commerson’s dolphins for Hg biomonitoring in the waters of the Subantarctic, which is a poorly studied region regarding Hg levels, sources and processes. Fil: Cáceres Saez, Iris. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales; Argentina. Museo Acatushún de Aves y Mamíferos Marinos Australes; Argentina Fil: Prosser Goodall, Rae Natalie. Consejo Nacional de ...